Real and hypothetical maximum potential scale ranges of most successful world decathlons - Bilic, M.; Smajlovic, N. (Acta Kinesiologica, 2015)
The paper presents the objectifying of criteria for evaluating the overall and individual achievements of the most successful decathlons in a world, as well as the type of structure the relationship between decathlon disciplines in relation to the achievements of the most successful athletes specialists. Obtained significant differences in performance levels and profile structure decathlon athletes and specialists, it has been ascertained that it is not appropriate to carry out structuring the relationship between discipline decathlon based on an assumed "ideal structure specialists" to permit a fuller expression of multidiscipline potential. However, based on established substantial uniformity of minimal results and maximum potential and approximate range of maximum uniformity of decathlon potential, obtained by natural objectified measuring scale allows reliable comparative assessment of the relationship between decathlon disciplines